41‐3: 17.3 Inch UHD Resolution AMOLED Panel Fabricated by Ink Jet Printing Process. Issue 1 (25th September 2020) - Chen, Peng-Yu; Chen, Chien-Chuan; Lin, Yu-Syuan; Li, Chun-Han; Hsieh, Hsieh-Tsung; Lu, Hsueh-Hsing; Chiang, Sin-Shen; Cheng, Robin; Chen, Nick. CC.; Jen, KR; Hsu, Daniel. CM.; Sun, Ming-Wei; et al.
Abstract : We fabricated a 17.3 inch AMOLED panel by using of the inkjet printing process. The panel resolution is UHD (3840x2160) and the pixel density is 255ppi (pixel per inch).The pixel design of the panel is real RGB side‐by‐side pixel arrangement. We demonstrated that the high resolution OLED panel could be realized with high efficiency material usage by inkjet printing process. Uniformity of top emission OLED structure and device performance including the luminous efficiency and the device lifetime is also discussed in our study.